A Preliminary Study on Dual Process Thinking in Marketing Education - Chan, Winslet T.Y; Leung , Chi-Hong (Asian Journal of Empirical Research, 2018)
Dual process thinking is an application of two systems of thinking for problem solving and decision-making. System 1 is a heuristic thinking system that involves intuitive and non-reflective thinking, prior knowledge and beliefs of decision maker. System 2 is an analytic thinking system that requires conscious effort and thought, numerical and logical reasoning. This study aims to investigate how marketing students solve problems with dual process thinking. Traditional Cognitive Reflection Test (CRT) contains three-item for measuring the tendency to override System 1 thinking and to engage in reflective System 2 thinking. While the traditional CRT is confounded with numeracy, which is not applicable to the field of marketing, this study employed traditional CRT with three additional marketing related measurement items to collect data from students who major in marketing for analysis. The analytical results showed that it is necessary to motivate and encourage marketing students to use System 2 thinking to learn different marketing concepts that are highly interrelated with one another and to complete tasks that require higher-order thinking skill. This paper also provides a useful reference for educators to design course assignments that aim to develop critical thinking and problem-solving skills of students.